An efficient cold-resistant strategy: Synthesis and application of green cold-resistant bio-based plasticizer for poly(vinyl chloride). (5th January 2021) - Liu, Dekai; Shen, Yirui; Jiang, Pingping; Thin Wai, Phyu; Zhang, Zheming; Zhang, Pingbo; Agus, Haryono; Nie, Zhixin; Zhao, Minzhong; Zhao, Huihang
Graphical abstract: The cold-resistant bio-based plasticizer is synthesized by oleic acid, and the PVC plasticized by these plasticizers possesses remarkable migration resistance and cold resistance. Highlights: There is no report about cold-resistant bio-based plasticizers, and this is the first one. Strong acid cation exchange resin is not only a catalyst, but also a ring opener for the following reaction. The PVC plasticized by these cold-resistant bio-based plasticizers basically does not migrate in various extreme environments. The PVC plasticized by these plasticizers exhibits outstanding cold resistance. Abstract: Nowadays, the most commonly used cold-resistant plasticizer, bis(2-ethylhexyl)adipate (DOA), not only has the poor migration resistance so that it can only be used as auxiliary plasticizer, but also causes huge pollution to the environment, especially water. Here, using renewable and green oleic acid as raw material, we had synthesized a series of oleate plasticizers. By means of capability tests, we detected that the Ti (initial degradation temperature) of PVC films plasticized with oleate plasticizers was 40 °C higher than that of DOA/PVC and 20 °C higher than that of DOTP/PVC. More importantly, in addition to illustrious migration resistance, they could maintain remarkable flexibility in cold environments as well. The low-temperature efficiency value of these oleate plasticizers exceeded 70 °C, which was much higher than DOTP and DOA. These results demonstrated that they possessed the potential to replace toxic DOP and poorly stable DOA, which provided an effective and green approach to solve the harm of plastic products to human health and the threat to the environment. In addition, these plasticizers broadened the application of PVC in cold environments, which was a boon for the application of PVC industry in the cold-resistant field, and contributed to sustainability of the hackneyed and oft-maligned PVC industry.